PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KINERJA MANAJERIAL PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN NGANJUK - INDRIAN SUPHENI; IKA NURIDA (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2017)
This study aims to determine the effect of Budgetary Arrangement, Organizational Commitment and Motivation on Managerial Performance On Revenue Office Financial Management And Regional Assets Nganjuk, either partially or simultaneously. Population in this research is all employees at DPPKAD Nganjuk district. The sample in this research is DPPKAD officer of Nganjuk district that is involved in the process of preparing the budget amounted to 30 samples. Sampling method using purposive sampling and data analysis method using multiple regression analysis.The results showed that the Participation of Budgeting, Organizational Commitment and Motivation partially affect the Manajaerial Performance. Participation of Budgeting, Organizational Commitment and Managerial Motivation simultaneously (together) have a significant effect on Managerial Performance with contribution rate of 91.36%.